How would you move Mount Fuji? : Microsoft's cult of the puzzle : how the world's smartest companies select the most creative thinkers - Poundstone, William (Boston : Little, Brown, 2003)
Microsoft's interview process is a grueling sequence of brain-busting questions that separate the most creative thinkers from the merely brilliant. So effective is their technique that other leading corporations--from the high-tech industry to consulting and financial services--are modeling their own hiring practices on Bill Gates' unique approach. How would you move Mount Fuji? reveals for the first time more than 35 of Microsoft's puzzles and riddles.
The impossible question -- The Termans and Silicon Valley -- Bill Gates and the Culture of Puzzles -- The Microsoft interview puzzles -- Embracing cluelessness -- Wall Street and the stress interview -- The hardest interview puzzles -- How to outsmart the puzzle interview -- How innovative companies ought to interview.
Includes bibliographical references (p. [257]-262) and index.
Keywords: Microsoft Corporation; Employment interviewing